2000
DOI: 10.1136/oem.57.11.786
|View full text |Cite
|
Sign up to set email alerts
|

Fungal and other spore counts as predictors of admissions for asthma in the Trent region

Abstract: Objectives-The importance of airborne fungal and other spores in provoking asthma attacks is uncertain. Panel studies have generated evidence that suggests a link between outdoor spore counts and severity of asthma. There have been no population based time series studies relating outdoor exposure to spores with incidence of attacks of asthma. Methods-Outcomes were hospital admissions for asthma on 2002 days during 1987-94, for children and adults in the Trent region of England. Predictors were daily counts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 30 publications
3
74
2
2
Order By: Relevance
“…The atmospheric concentrations reported for DDS in the size range of 2-10 µm are mostly on the order of 10 3 -10 4 m −3 , i.e. comparable to the average concentrations of ABS and AAS (Gregory and Hirst, 1957;Gregory and Sreeramulu, 1958;Adams et al, 1968;Chatterjee and Hargreave, 1974;Kramer and Eversmeyer, 1984;Li and Kendrick, 1995;Newson et al, 2000;Troutt and Levetin, 2001;Levetin, 2004;Wu et al, 2004;Fang et al, 2005;Ho et al, 2005;Zoppas et al, 2006).…”
Section: Wet and Dry Discharged Sporesmentioning
confidence: 99%
See 4 more Smart Citations
“…The atmospheric concentrations reported for DDS in the size range of 2-10 µm are mostly on the order of 10 3 -10 4 m −3 , i.e. comparable to the average concentrations of ABS and AAS (Gregory and Hirst, 1957;Gregory and Sreeramulu, 1958;Adams et al, 1968;Chatterjee and Hargreave, 1974;Kramer and Eversmeyer, 1984;Li and Kendrick, 1995;Newson et al, 2000;Troutt and Levetin, 2001;Levetin, 2004;Wu et al, 2004;Fang et al, 2005;Ho et al, 2005;Zoppas et al, 2006).…”
Section: Wet and Dry Discharged Sporesmentioning
confidence: 99%
“…They also reported that dry discharged fungal spores (DDS) were enhanced during warm, dry weather conditions, whereas actively wet discharged AAS and ABS concentrations tend to be enhanced during humid conditions, such as those at night and in the early morning. Most studies of total fungal spores in continental air around the world have reported concentrations on the order of 10 4 m −3 (Newson et al, 2000;Troutt and Levetin, 2001;Wu et al, 2004;Ho et al, 2005;Zoppas et al, 2006).…”
Section: Wet and Dry Discharged Sporesmentioning
confidence: 99%
See 3 more Smart Citations